Management of Graves' hyperthyroidism: present and future. Issue 2 (4th March 2022) - Bartalena, Luigi; Piantanida, Eliana; Gallo, Daniela; Ippolito, Silvia; Tanda, Maria Laura
ABSTRACT: Introduction: Graves' disease (GD) is an autoimmune disorder due to loss of tolerance to the thyrotropin receptor (TSHR) and ultimately caused by stimulatory TSHR antibodies (TSHR-Ab). GD may be associated with extrathyroidal manifestations, mainly Graves' orbitopathy. Treatment of GD relies on antithyroid drugs (ATDs), radioactive iodine (RAI), thyroidectomy. The major ATD limitation is the high recurrence rate after treatment. The major drawback of RAI and thyroidectomy is the inevitable development of permanent hypothyroidism. Areas covered: Original articles, clinical trials, systematic reviews, meta-analyses from 1980 to 2021 were searched using the following terms: Graves' disease, management of Graves' disease, antithyroid drugs, radioactive iodine, thyroidectomy, Graves' orbitopathy, thyroid-eye disease. Expert opinion: ATDs are the first-line treatment worldwide, are overall safe and usually given for 18–24 months, long-term treatment may decrease relapses. RAI is safe, although associated with a low risk of GO progression, particularly in smokers. Thyroidectomy requires skilled and high-volume surgeons. Patients play a central role in the choice of treatment within a shared decision-making process. Results from targeted therapies acting on different steps of the autoimmune process, including iscalimab, ATX-GD-59, rituximab, blocking TSHR-Ab, small molecules acting as antagonists of the TSHR, are preliminary or preclinical, but promising in medium-to-long perspective.